Comparison of antiurolithic effect of some medicinal plants (Paronychia argentea and Adiantum capillus veneris) with locally marketed herbal medicines - زاهر , سارة; ريم سلامة , (Latakia University Journal -Medical Sciences Series, 2024)
Urolithiasis is a polygenic disorder with complex etiology and complicated treatment outcomes. Adiantum capillus veneris and Paronychia argentea are widely spread crops with traditional claims for its antiurolithiatic potential. The present study was an attempt to investigate the antilithic potential of aqueous extract of Adiantum capillus veneris and Paronychia argentea and locally marketed medication against calcium oxalate (CaOx) urolithiasis by employing in vitro methods. Nucleation, growth and aggregation assay of CaOx crystallization were used. In the Nucleation and aggregation stage, the aqueous extract of Adiantum capillus veneris showed the highest inhibition, followed by the medication extract, then the extract of Paronychia argentea. During the growth phase, the aqueous extract of medication demonstrated the highest inhibition, followed by the Adiantum capillus veneris extract, then the Paronychia argentea extract. Aqueous extract of Adiantum capillus veneris and Paronychia argentea possess significant antiurolithiatic activity against CaOx urolithiasis in vitro which could be attributed to its active components like saponins, tannins, flavonoids and phenolic content.